Pengaruh Guided Imagery terhadap Tingkat Kecemasan dan Depresi Ibu Hamil Selama Pandemi Covid 19 di Puskesmas Koni Kota Jambi - Herinawati Herinawati; Diniyati Diniyati; Iksaruddin Iksaruddin; Melyana Nurul Widyawati (Jurnal Akademika Baiturrahim Jambi, 2023)
One of the most vulnerable groups during the coronavirus-19 outbreak is pregnant women. Pregnant women are more prone to anxiety because they see about vertical spread to the fetus. Disturbance during mental health is a common morbidity of pregnancy, about 12% of women experience depression and up to 22% experience high levels of anxiety in late pregnancy. Another study related to anxiety and depression during the pandemic in Turkey in 2019 stated that the Covid-19 outbreak negatively affected the mental health of pregnant women which in turn could harm pregnant women. Problems during pregnancy can be overcome by using non-pharmacological therapy. One of the non-pharmacological techniques is Guided Imagery. Guided imagery or guided imagination technique is the development of mental functions that are expressed dynamically through psychophysiological processes involving all senses and leading to changes in behavior, perception, or physiological responses with someone's guidance or through the media. Methods The research conducted at the Koni Health Center in Jambi City, will be carried out from January to November 2021 with a total of 40 respondents. Quantitative research using a quasi-experimental design with One Group Pretest Posttest Design is to measure the effect (effect) of an intervention carried out on research subjects. Collecting data from primary data obtained from questionnaires. Research Results There is an effect of anxiety level and depression level of pregnant women before and after being given guided imagery. Hopefully, the results of this study will serve as another alternative in providing midwifery care in an effort to overcome anxiety and depression in pregnant women during the Covid-19 pandemi